The Status of Adopted Children and Its Implications in Islamic Family Law - Melinda Meicha; Nur Hamimah; Nemi Hulayat Nemi Hulayat; Fadilah Syafitra Fadilah Syafitra; Islahul Balad Islahul Balad (Sekolah Tinggi Agama Islam Solok Nan Indah, 2026)
This study examines the legal status of adopted children within the framework of Islamic family law, particularly concerning lineage (nasab), guardianship, and inheritance (fara'id). The study aims to analyze the legal status of adopted children from the perspective of Islamic family law and to explain its implications for family relationships and civil rights. This study employed a qualitative doctrinal legal research design combined with qualitative content analysis. Documentary data were obtained from primary legal sources, including the Quran, Hadith, the Compilation of Islamic Law (Kompilasi Hukum Islam), and relevant Indonesian legislation, as well as secondary legal sources comprising peer-reviewed journal articles, scholarly books, legal commentaries, court decisions, and other academic publications. Data were collected through a systematic document review and analyzed using qualitative content analysis involving thematic coding, legal interpretation, and comparative analysis. The findings indicate that adoption under Islamic family law does not alter the child's biological lineage and therefore does not establish legal consequences equivalent to those of biological children with respect to guardianship and inheritance. The study further finds that the protection of adopted children is realized through the principles of kafalah, hibah, wasiat, and wasiat wajibah, which provide mechanisms for safeguarding their civil rights while preserving biological lineage. In the Indonesian context, the legal framework governing adopted children reflects an effort to harmonize Islamic legal principles with child protection, although challenges remain regarding regulatory inconsistencies, legal implementation, and public legal literacy